Special issue “Novel research about biomechanics and biomaterials used in hip, knee and related joints”: editorial - Kretzer, Jan Philippe; Van Der Straeten, Catherine (Materials, 2021)
Joint replacement is a very successful medical treatment [...]
Gesehen am 30.06.2021